CLASSIFICATION OF PROBLEMS ENCOUNTERED IN THE TRANSLATION PROCESS - Tuyboeva Shakhnoza; Mo’minjonova Mashxura Moxirjon qizi (Web of Journals Publishing, 2025)
This thesis discusses some syntactic phenomena encountered in the process of translation of works of fiction in French and Uzbek, a comparative analysis of their similarities and differences, and a proposal for strategies for preserving or adapting these phenomena.
Keywords: Fiction, translation problems, french language, uzbek language, similarities, differences, grammar, syntactic phenomenon, classification, semantics.